2017
DOI: 10.1002/anie.201707553
|View full text |Cite
|
Sign up to set email alerts
|

Benzodisilacyclobutadienes: 8π‐Electron Systems with an Antiaromatic Silicon Ring

Abstract: Benzodisilacyclobutadienes 2 a-c were isolated as blue to green crystalline solids from the reaction of stable disilyne 1 and 1,2-dibromobenzenes in the presence of potassium graphite. In the solid state, substantial bond alternation was observed within the benzene rings of 2 a-c. In hexane, 2 a-c showed remarkable bathochromic shifts of the π→π* (HOMO→LUMO) absorption bands at 625-670 nm. NMR spectra and theoretical calculations indicated that the diamagnetic ring currents of the benzene rings of 2 a-c are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Matsuo’s group reported that silicon and germanium analogues of cyclobutadiene ( VII ) are nonaromatic with a rhombic structure . Recently, a benzodisilacyclobutadiene ( VIII ) was proved to have an 8π-antiaromatic character by NMR spectroscopic, structural, and theoretical studies …”
mentioning
confidence: 99%
“…Matsuo’s group reported that silicon and germanium analogues of cyclobutadiene ( VII ) are nonaromatic with a rhombic structure . Recently, a benzodisilacyclobutadiene ( VIII ) was proved to have an 8π-antiaromatic character by NMR spectroscopic, structural, and theoretical studies …”
mentioning
confidence: 99%
“…Like the present work, that paper predicts four equal SiC distances in the alternating ring. A compound with adjacent doubly bonded Si atoms in a 4-membered ring has recently been isolated, by including its two adjacent carbon atoms into a 6-atom carbon ring, as part of a bicyclic C 6 Si 2 8π electron system. Thus, no parent or substituted alternating H 4 Si 2 C 2 appears to be known in the laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…Ther eduction of an equimolar mixture of dialkyldisilyne 1, [14] which contains bulky Rs protecting groups [Rs = 1,1bis(trimethylsilyl)-3,3-dimethylbutyl],a nd 1,2-dibromobenzene with potassium graphite (KC 8 ;2 .2 equiv) in 1,2-dimethoxyethane (DME) at À40 8 8Ca fforded 2a as ab lue crystalline solid in 40 %yield (Scheme 1). Similarly,the corresponding dimethyl (2b)a nd dimethoxy derivatives (2c)w ere isolated as blue and green crystalline solids in 27 and 23 % yield, respectively.T he molecular structures of 2a-c were unequivocally determined by multinuclear NMR spectroscopy,m ass spectrometry,e lemental analysis,a nd single-crystal X-ray diffraction (XRD) analysis.A lthough the detailed reaction mechanism that leads to the formation of 2a-c remains unclear at this point, the reaction could be initiated by the reduction of disilyne 1,g iven that Sekiguchi and coworkers have reported that the one-electron reduction of disilynes affords the corresponding anion radical.…”
Section: Benzannulated Cyclobutadienes (Benzocyclobutadienes)mentioning
confidence: 99%